The BET protein inhibitor apabetalone (RVX-208) restores angiogenic response in type 1 and type 2 diabetes by transcriptional regulation of thrombospondin-1. (14th October 2021) - Mohammed, S; Mattia, M A; Gergely, G K; Gaia, G S; Ambrosini, S A; Paolo, P M; Thomas F, T F L; Sarah, S C; Gian Paolo, G P F; Francesco, F P
Abstract: Background: Peripheral artery disease (PAD) is highly prevalent in people with type 2 diabetes and associates with chronic limb ischemia and poor prognosis. Understanding the mechanisms of impaired blood vessel growth in diabetic patients is of paramount importance to develop new angiogenic therapies in this setting. Dysregulation of epigenetic mechanisms of gene transcription in vascular cells contributes to cardiovascular disease development but is currently not targeted by therapies. Apabetalone (RVX-208) – an FDA approved small molecule inhibitor of the epigenetic readers bromodomain and extra-terminal (BET) proteins – has recently shown to modulate transcriptional programs implicated in vascular inflammation and atherosclerosis. Purpose: To investigate RVX-208 effects in modulating angiogenic response and post-ischemic vascularization in diabetes. Methods: Primary human aortic endothelial cells (HAECs) were exposed to normal glucose (NG, 5 mM) or high glucose (HG, 20 mM) for 48 hours in presence of RVX-208 (20μM) or vehicle (DMSO). Scratch and tube formation assays were performed to investigate the impact of RVX-208 on angiogenic properties of HAECs. T1D mice (streptozotocin-induced diabetes) and T2D mice (Lepdb/db) were orally treated with apabetalone or vehicle for 5 days. Hindlimb ischemia was induced in T1D mice & blood flow recovery analysed at 30 minutes, 7 and 14 days by laser Doppler imaging. Sprouting and matrigel plug assays were performed in Lepdb/db mice. Gastrocnemius muscle samples from patients with and without T2D were employed to translate our experimental findings. Results: HG impaired HAECs migration and tube formation as compared to NG, whereas treatment with RVX-208 rescued HG-induced impairment of angiogenic properties. Real time PCR arrays in HG-treated HAECs showed that RVX-208 treatment prevents the dysregulation of genes implicated in endothelial migration, sprouting and inflammation, namely the anti-angiogenic molecule thrombospondin (THBS1), VEGF-A, IL-1β, IL-6, VCAM-1, and CXCL1. Of interest, both gene silencing of BET protein (BRD4) or its pharmacological inhibition by RVX-208 reduced THBS1 expression while restoring VEGFA levels in HG-treated HAECs. ChIP assays showed the enrichment of both BRD4 and the active chromatin mark H3K27Ac on THBS1 promoter. Mechanistic experiments uncovered the inhibitory role of THBS1 on VEGFA signalling, as also confirmed by STRING analysis. Treatment of T1D mice with RVX-208 improved blood flow reperfusion and vascular density at 14 days as compared to vehicle-treated animals. Moreover, RVX-208 restored endothelial sprouting in T2D-Lepdb/db mice. Of clinical relevance, THBS1 was upregulated while VEGFA expression was reduced in gastrocnemius muscle specimens from T2D patients with PAD as compared to non-diabetic controls. Conclusion: In vivo targeting of BET-proteins by RVX-208 may represents a novel therapeutic approach to boost post-ischemic neovascularization in diabetes. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): University of Zurich